To calculate the expression 3 * 4 ^ 2 + 8 - 6/2, we follow the order of operations (also known as PEMDAS), which stands for Parentheses, Exponents, Multiplication and Division (from left to right), and Addition and Subtraction (from left to right).
First, we evaluate the exponent: 4 ^ 2 = 16.
Next, we multiply 3 by the result of the exponent: 3 * 16 = 48.
Afterward, we deal with the division: 6/2 = 3.
Finally, we add and subtract the remaining terms: 48 + 8 - 3 = 53.
Therefore, 3 * 4 ^ 2 + 8 - 6/2 equals 53.
3 * 4 ^ 2 + 8 - 6/2
3 answers
The 6/2 is not divided it’s a fraction
Apologies for the confusion. If the expression is 3 * 4^2 + 8 - 6/2 as a fraction, we first calculate the exponent: 4^2 = 16.
Next, we simplify the fraction: 6/2 = 3.
Then, we perform the multiplication: 3 * 16 = 48.
Finally, we add and subtract the remaining terms: 48 + 8 - 3 = 53.
Therefore, 3 * 4^2 + 8 - 6/2 (as a fraction) equals 53.
Next, we simplify the fraction: 6/2 = 3.
Then, we perform the multiplication: 3 * 16 = 48.
Finally, we add and subtract the remaining terms: 48 + 8 - 3 = 53.
Therefore, 3 * 4^2 + 8 - 6/2 (as a fraction) equals 53.